Fracture Resistance of Primary Molars Restored with Endocrowns Versus Zirconia Crowns (An in Vitro Study) - Sabbah, Ayman; Kamel, Mostafa (Brazilian Dental Science, 2021)
Objective: This study aimed to assess the fracture resistance of primary molars restored with endocrowns compared to prefabricated zirconia crowns. Methods: Twelve sound, defect-free primary second molars were selected and divided into two groups: group I included 6 molars restored with zirconia crowns, while group II included 6 teeth restored with endocrowns. For both groups access cavity was prepared for the teeth to open pulp chamber. Fracture resistance of both groups was tested using a universal testing machine. Results: Zirconia crown showed statistically significantly higher mean fracture resistance than Endocrown (P-value = 0.001, Effect size = 2.72). Conclusion: Pulpotomized primary molars restored with Zirconia crowns showed significantly higher mean fracture resistance compared to primary molars restored with endocrowns, meanwhile both restorations have shown higher mean fracture resistance than the maximum biting force in children. Keywords Composite resins; Endocrown; Fracture strength; Zirconia crowns.